The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/ppap.200400011
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Plasma‐Surface Interactions During Processing of Polymeric Materials Measured Using the IRIS Technique

Abstract: Summary: This work reviews the use of the imaging of radicals interacting with surfaces (IRIS) technique to elucidate chemical mechanisms during plasma modification of polymers. Four systems are examined, NH and NH2 in NH3 plasmas, OH radicals in H2O and O2/NH3 plasmas, OH in SiO2 film deposition systems, and CF2 molecules in a variety of fluorocarbon plasmas. Some of the findings include that NH and NH2 are produced at the surface during NH3 plasma modification of polymers. Their surface interactions are dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Experiments using space-and time-resolved, laser-induced fluorescence (LIF) and absolute calibration techniques [48,49] have established that CF and CF 2 radicals are produced essentially at the surfaces, and that the actual film precursors are oligomers of the C x F y (CF 2 ) n type formed in gas-phase polymerization reactions of the relatively abundant CF 2 radicals. The production of CF 2 at the surface of the forming FC films, and the low sticking probability of the radical, were also observed by Fisher and co-workers, [50] who conducted detailed experiments on various plasma precursors using the "imaging of radicals interacting with surfaces" (IRIS) technique, [51] which combines molecular beams and LIF imaging methods. The enhancement in CF 2 production through ion bombardment has also been investigated by this group.…”
Section: Francisco José Gordillomentioning
confidence: 79%
See 1 more Smart Citation
“…Experiments using space-and time-resolved, laser-induced fluorescence (LIF) and absolute calibration techniques [48,49] have established that CF and CF 2 radicals are produced essentially at the surfaces, and that the actual film precursors are oligomers of the C x F y (CF 2 ) n type formed in gas-phase polymerization reactions of the relatively abundant CF 2 radicals. The production of CF 2 at the surface of the forming FC films, and the low sticking probability of the radical, were also observed by Fisher and co-workers, [50] who conducted detailed experiments on various plasma precursors using the "imaging of radicals interacting with surfaces" (IRIS) technique, [51] which combines molecular beams and LIF imaging methods. The enhancement in CF 2 production through ion bombardment has also been investigated by this group.…”
Section: Francisco José Gordillomentioning
confidence: 79%
“…The enhancement in CF 2 production through ion bombardment has also been investigated by this group. [50,52] Other aspects of the behavior of CF x radicals in fluorocarbon plasmas are presently being studied by various groups. [53,54] and CN were found to be "sticky" with high surface reactivity, whereas NH and SiCl 2 do not tend to stick to the surface of growing films.…”
Section: Francisco José Gordillomentioning
confidence: 99%
“…Experiments using space and time resolved laser induced fluorescence (LIF) and absolute calibration techniques [48,49] have established that CF and CF 2 radicals are produced essentially at the surfaces, and that the actual film precursors are oligomers of the C x F y (CF 2 ) n type formed in gas phase polymerization reactions of the relatively abundant CF 2 radicals. The production of CF 2 at the surface of the forming FC films, and the low sticking probability of the radical were also observed by Fisher and co-workers, [50] who conducted detailed experiments on different plasma precursors using the "imaging of radicals interacting with surfaces" (IRIS) technique, [51] which combines molecular beams and LIF imaging methods. The enhancement in CF 2 production through ion bombardment has also been investigated by this group.…”
mentioning
confidence: 79%
“…2). Previously, it has been shown that nitrogen plasma treatment of parylene (50 W, for $30 s) promoted surface reactivity and hydrophilicity, a general trend in hydrophobic polymers [33][34][35] ; here, the high energy required (associated with 150 W of power for 15 min) to etch channels in parylene had significantly altered surface morphology, possibly effecting charging characteristics.…”
Section: Electro-osmotic Mobilitymentioning
confidence: 96%
“…2, #3, for 20 days). Hydrophobic recovery was observed in plasma treatment of diverse polymer surfaces [33] , and was associated with, e.g., charge redistribution and=or adsorption events [37] . Due to their complex nature, these phenomena are not discussed here; however, the results indicate that the recovery also happens in the plasma etched parylene substrates, even at the relatively high power used to etch the substrates.…”
Section: Electro-osmotic Mobilitymentioning
confidence: 99%